The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3946/kjme.2021.190
|View full text |Cite
|
Sign up to set email alerts
|

Assessing webinar outcomes for health professionals: a perspective from Indonesia during coronavirus disease 2019 pandemic

Abstract: Purpose With the ongoing coronavirus disease 2019 (COVID-19) pandemic, health institutions and hospitals are increasingly relying on e-learning for continuing education. However, in many countries there is still limited data on the effectiveness of online learning particularly in the healthcare field. This study aims to evaluate whether webinar as a form of online educational intervention is satisfactory and effective for the continuing education of health professionals in Indonesia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
2
12
0
3
Order By: Relevance
“…The questions in the knowledge test covered clinical aspects of various diseases encountered in daily practice, which included their etiology, pathophysiology and pathogenesis, signs and symptoms, diagnosis, management, and prevention. This result further supported the findings in our previous study, in which we also discovered that physicians who graduated more recently (2015–2020) had higher average post-test scores than physicians who graduated in 2014 or prior in all six webinars [ 11 ]. We hypothesized that most recently graduated physicians could engage better with the webinar series and hence absorbed the material better than senior physicians.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The questions in the knowledge test covered clinical aspects of various diseases encountered in daily practice, which included their etiology, pathophysiology and pathogenesis, signs and symptoms, diagnosis, management, and prevention. This result further supported the findings in our previous study, in which we also discovered that physicians who graduated more recently (2015–2020) had higher average post-test scores than physicians who graduated in 2014 or prior in all six webinars [ 11 ]. We hypothesized that most recently graduated physicians could engage better with the webinar series and hence absorbed the material better than senior physicians.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, ensuring interactivity in learning is arguably one of the biggest challenges in conducting an online CME course. Although the i-CORPS webinar series has anticipated this problem by encouraging the instructors to be engaging, for example, using the “chat” and “polling” features in Zoom [ 11 ], this remains a limitation worth considering for future online CME courses. An interactive learning experience was associated with better knowledge retention, and failure to establish a two-way communication involving feedback may negatively affect participants’ attention span and retention level [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formerly, other studies assessed the evidence regarding the benefits of webinar teaching as an educational intervention for health professionals. Edward Christopher Yo et al (27) mentioned that the use of webinars for health professionals training in Indonesia was wellreceived amidst the outbreak pandemic. Also, Bhattarai et al (28) reported that teaching through a webinar was an invaluable instrument for medical education, particularly during the need of social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Against the backdrop of the pandemic, webinars have become popular alternatives amongst PGs to regular departmental seminars, although the attendance rate is variable. [ 18 ]…”
Section: Webinarsmentioning
confidence: 99%